OPTIMASI TEKNOLOGI PRODUKSI BENIH KENTANG VERIETAS CP3 MELALUI PENGATURAN JARAK TANAM DAN APLIKASI PGPR DI LAPANGAN - Hardiana Usman; Netty Netty; Sudirman Numba (Percetakan Umi Toaha Makassar, 2026)
Increasing potato seed production requires implementing appropriate cultivation technologies, particularly in plant spacing management and the use of biological agents such as Plant Growth-Promoting Rhizobacteria (PGPR). This study aimed to analyze the interaction effect between plant spacing and PGPR application on the growth and yield of CP3 potato seed under field conditions and to determine the optimal treatment combination for producing small-sized tubers suitable for seed purposes. The research was conducted from August to December at P4S Bulu Ballea, Gowa Regency, located at an altitude of approximately 1,200 m above sea level, using a two-factor Randomized Block Design (RBD) with three replications. The first factor consisted of plant spacing (40 cm × 30 cm, 40 cm × 20 cm, and 40 cm × 10 cm), while the second factor was PGPR concentration (20, 30, and 40 ml l⁻¹). The observed parameters included plant height, number of leaves, stem diameter, number of branches, tuber diameter, number of tubers per plant, tuber weight per plant, tuber weight per plot, and productivity per hectare. Data were analyzed using analysis of variance (ANOVA) followed by the Honestly Significant Difference (HSD) test at the 5% significance level. The results showed that PGPR application significantly affected plant height (92.04 cm) and tuber diameter (7.74 mm), whereas plant spacing significantly influenced the number of branches (3.29 branches), tuber length (7.03 cm), tuber diameter (53.30 mm), tuber weight per plant (99.81 g), tuber weight per plot (1,083.00 g), and yield (10.83 t ha⁻¹). The closest spacing (40 cm × 10 cm) produced tuber sizes suitable for seed production. These findings indicate that optimizing plant spacing and PGPR application synergistically enhances CP3 potato seed production under field conditions.